2016
DOI: 10.5130/ajceb.v16i1.4813
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of floor construction on sloping sites: an analysis of cumulative energy demand and greenhouse gas emissions

Abstract: In order to make environmentally aware decisions, there is growing interest in the comparative energy and greenhouse gas (GHG) performance of competing construction methods. Little research has been done concerning competing ground floor construction methods, especially given different site variables, such as slope and soil type. A life cycle assessment approach was adopted to analyse environmental impacts, including cumulative energy demand and GHG emissions for detached housing construction in Australia. Dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…In this study, "sufficient information" was defined as information on the built area, the reference study period and the total embodied GHG emissions. From the in-depth analysis, 79 papers and reports were found relevant (Salazar and Meil, 2009;Sodagar et al, 2011;Hoxha et al, 2020), (Buchanan and Honey, 1994;Buchanan and Levine, 1999;Börjesson and Gustavsson, 2000;Aye et al, 2012;Dahlstrøm et al, 2012;Brown et al, 2013;Buchanan et al, 2013;Darby et al, 2013;Ajayi et al, 2015;Fouquet et al, 2015;Ding and Forsythe, 2016;Skullestad et al, 2016;Balasbaneh and Bin Marsono, 2017;Amiri Fard et al, 2019;Emami et al, 2019;Svortevik et al, 2020), Gerilla et al, 2007;Frenette et al, 2008;Gustavsson and Joelsson, 2010;Kahhat et al, 2011;Griffin et al, 2013;Fu et al, 2014;Grant et al, 2014;Islam et al, 2015;Liu et al, 2016;Häfliger et al, 2017;Lessard et al, 2018;Kamali et al, 2019;Rønning et al, 2019), (Peuportier, 2001;Monahan and Powell, 2011;Nässén et al, 2012;Van Ooteghem and Xu, 2012;Damvad Analytics, 2016;Larsson et al, 2016;Motuzienė et al, 2016;…”
Section: Data Filtering Process and Exclusion Criteriamentioning
confidence: 99%
“…In this study, "sufficient information" was defined as information on the built area, the reference study period and the total embodied GHG emissions. From the in-depth analysis, 79 papers and reports were found relevant (Salazar and Meil, 2009;Sodagar et al, 2011;Hoxha et al, 2020), (Buchanan and Honey, 1994;Buchanan and Levine, 1999;Börjesson and Gustavsson, 2000;Aye et al, 2012;Dahlstrøm et al, 2012;Brown et al, 2013;Buchanan et al, 2013;Darby et al, 2013;Ajayi et al, 2015;Fouquet et al, 2015;Ding and Forsythe, 2016;Skullestad et al, 2016;Balasbaneh and Bin Marsono, 2017;Amiri Fard et al, 2019;Emami et al, 2019;Svortevik et al, 2020), Gerilla et al, 2007;Frenette et al, 2008;Gustavsson and Joelsson, 2010;Kahhat et al, 2011;Griffin et al, 2013;Fu et al, 2014;Grant et al, 2014;Islam et al, 2015;Liu et al, 2016;Häfliger et al, 2017;Lessard et al, 2018;Kamali et al, 2019;Rønning et al, 2019), (Peuportier, 2001;Monahan and Powell, 2011;Nässén et al, 2012;Van Ooteghem and Xu, 2012;Damvad Analytics, 2016;Larsson et al, 2016;Motuzienė et al, 2016;…”
Section: Data Filtering Process and Exclusion Criteriamentioning
confidence: 99%
“…Projects situated on steep sites are also excluded from the study as they will require more energy dependent heavy materials when compared to timber during the earthworks stage (Ding & Forsythe 2016). The study also showed that greater energy was required for earthworks in highly reactive soil or rock for heavy materials compared to timber houses.…”
Section: Case Study Projectsmentioning
confidence: 99%